Differential and variational formalism for an acoustically levitating drop - Chernova, M.O.; Lukovsky, I.O.; Tymokha, O.M. (Нелінійні коливання, 2015)
Starting with the most general problem on interface waves between two ideal fluids, treated here as an ullage gas and a liquid, respectively, and separating fast and slow time scales, differential and variational formalism for an acoustically levitating drop and its time-averaged shape (the drop vibroequilibrium) are developed. The drop vibroequilibria can differ from spherical shape; stable vibroequilibria are associated with local minima of the quasipotential energy whose analytical form is also derived in the present paper Починаючи з найбiльш загальної задачi про iнтерфейснi хвилi мiж двома iдеальними рiдинами, що розглядаються як газ та рiдина вiдповiдно, i вiддiляючи швидкi та повiльнi часовi шкали, розвинено диференцiальний та варiацiйний формалiзм для акустично левiтуючої краплi та знайдено її усереднену за часом форму (вiброрiвноважний стан). Вiброрiвноважнi стани краплi можуть вiдрiзнятися вiд сферичної форми; стiйкi вiброрiвноважнi стани пов’язанi з локальними мiнiмумами квазiпотенцiальної енергiї, для якої також побудовано аналiтичне зображення.